Influence of Salary and Promotion on Academic Staff ’ s Job Performance in Tanzanian Universities - Ngalomba, Simon Peter (Papers in Education and Development, 2022)
Abstract Salary and promotion practices for academic staff in universities has been a subject of concern for long time as there is a mass exodus of academic staff to other seemingly financially promising non-teaching careers. The study therefore, examined academic staff ' s ' salary and promotion practices and assessed the extent to which they influence their job performance. The study adopted a correlational research design. The data for this study were collected using questionnaires from 411 academic staff in selected Tanzanian universities. Semistructured interviews were conducted with six Deputy Vice Chancellors €“ Administration, 12 senior academic staff and two leaders of the academic staff union. Purposive sampling was used to select universities. The data were analysed using Statistical Package for Social Sciences (SPSS) version 16. The findings indicated that there is no statistically significant relationship between salary, promotion and job performance among university academic staff. Keywords: competitive compensation, research, teaching, universities, workload